ANALYSIS OF THE COMPETITIVE MARKET SITUATION FOR SHAPING THE STRATEGIC DEVELOPMENT VECTOR OF THE ENTERPRISE - Iryna V. Taranenko; Volodymyr S. Naumenko; Valentyna M. Shevchenko; Svitlana S. Yaremenko (Academy Review)
During the war, enterprises providing services for the repair of electrical equipment found themselves in conditions of uncertainty and instability. Therefore, these enterprises should clearly define their strategic development vector depending on their size, geographical location, and specialization, taking into account the competitive situation in the market. The article examines the main dynamics of the Ukrainian market for electrical equipment repair services for the period from 2016 to 2022. The study’s results showed that, before the start of the full-scale war, the market experienced steady growth and profitability due to the fact that demand for electrical equipment repair services came from all enterprises using electrical equipment, as well as organizations and households. In 2022, under the influence of the full-scale invasion, the number of enterprises, the volume of products sold, and the profitability of operational activities significantly decreased. The results of the market analysis of industrial electrical equipment repair services in the Dnipropetrovsk region, using the Herfindahl-Hirschman index, indicated a low market concentration. The industry competition analysis, using M. Porter’s 5 forces model, showed that barriers to entry into the industry are low, with service differentiation being more typical of medium-sized enterprises. Small and, especially, micro-enterprises provide more standardized services. Taking into account the identified features and trends in the development of the electrical equipment repair market, as well as the competitive situation, which is characterized by low concentration, a large number of enterprises providing similar but not identical services, and low barriers to entry – leading to significant free entry into the industry for other firms—it is concluded that monopolistic competition exists in the market. Based on the results of the analysis, the following main strategic development vectors for domestic enterprises operating in the electrical industrial equipment repair market were determined: expanding their presence and service implementation in the region; entering other regions within the country; mastering new types of electrical equipment repair; and entering the foreign market. The choice of specific development vectors is substantiated depending on the time horizon, size, and market opportunities of a specific enterprise.